Bronchiectasis in India: results from the European Multicentre Bronchiectasis Audit and Research Collaboration (EMBARC) and Respiratory Research Network of India Registry. Issue 9 (September 2019) - Dhar, Raja; Singh, Sheetu; Talwar, Deepak; Mohan, Murali; Tripathi, Surya Kant; Swarnakar, Rajesh; Trivedi, Sonali; Rajagopala, Srinivas; D'Souza, George; Padmanabhan, Arjun; Baburao, Archana; Mahesh, Padukudru Anand; et al.
Summary: Background: Bronchiectasis is a common but neglected chronic lung disease. Most epidemiological data are limited to cohorts from Europe and the USA, with few data from low-income and middle-income countries. We therefore aimed to describe the characteristics, severity of disease, microbiology, and treatment of patients with bronchiectasis in India. Methods: The Indian bronchiectasis registry is a multicentre, prospective, observational cohort study. Adult patients (≥18 years) with CT-confirmed bronchiectasis were enrolled from 31 centres across India. Patients with bronchiectasis due to cystic fibrosis or traction bronchiectasis associated with another respiratory disorder were excluded. Data were collected at baseline (recruitment) with follow-up visits taking place once per year. Comprehensive clinical data were collected through the European Multicentre Bronchiectasis Audit and Research Collaboration registry platform. Underlying aetiology of bronchiectasis, as well as treatment and risk factors for bronchiectasis were analysed in the Indian bronchiectasis registry. Comparisons of demographics were made with published European and US registries, and quality of care was benchmarked against the 2017 European Respiratory Society guidelines. Findings: From June 1, 2015, to Sept 1, 2017, 2195 patients were enrolled. Marked differences were observed between India, Europe, and the USA. Patients in India were younger (median age 56 years [IQR 41–66] vs the European and US registries; p<0·0001]) and more likely to be men (1249 [56·9%] of 2195). Previous tuberculosis (780 [35·5%] of 2195) was the most frequent underlying cause of bronchiectasis and Pseudomonas aeruginosa was the most common organism in sputum culture (301 [13·7%]) in India. Risk factors for exacerbations included being of the male sex (adjusted incidence rate ratio 1·17, 95% CI 1·03–1·32; p=0·015), P aeruginosa infection (1·29, 1·10–1·50; p=0·001), a history of pulmonary tuberculosis (1·20, 1·07–1·34; p=0·002), modified Medical Research Council Dyspnoea score (1·32, 1·25–1·39; p<0·0001), daily sputum production (1·16, 1·03–1·30; p=0·013), and radiological severity of disease (1·03, 1·01–1·04; p<0·0001). Low adherence to guideline-recommended care was observed; only 388 patients were tested for allergic bronchopulmonary aspergillosis and 82 patients had been tested for immunoglobulins. Interpretation: Patients with bronchiectasis in India have more severe disease and have distinct characteristics from those reported in other countries. This study provides a benchmark to improve quality of care for patients with bronchiectasis in India. Funding: EU/European Federation of Pharmaceutical Industries and Associations Innovative Medicines Initiative inhaled Antibiotics in Bronchiectasis and Cystic Fibrosis Consortium, European Respiratory Society, and the British Lung Foundation.